Hubungan Pola Asuh Orang Tua dengan Self-Esteem pada Remaja di SMA Negeri 2 Gading Rejo - Purwanty, Sulistya; Agustriyani, Feri; Ardinata, Ardinata; Palupi, Rini; Mukhlis, Hamid (Penerbit Goodwood, 2023)
Purpose: Adolescence is a phase that will certainly be experienced by an adolescent, which is characterized by biological, psychological, and social changes. According to The World Health Organization (WHO), the prevalence of people with emotional and mental disorders in the world reaches 16% with vulnerable ages 10-19 years starting at the age of 14 years. Adolescents with a high level of self-esteem tend to demonstrate positive qualities and behaviors. Parent parenting has a very important role in determining the nature and behavior of an adolescent. The implementation of effective and appropriate parenting styles contributes to the development of a high level of self-esteem in children. This study aimed to investigate the correlation between parenting styles and self-esteem among adolescents at SMA Negeri 2 Gading Rejo. Methodology: The quantitative research method employed a Cross-Sectional Research Design, and the sampling technique was Cluster Random Sampling. Additionally, the data collection technique employed a Likert scale questionnaire. The sample of this study was 78 respondents. Results: The bivariate analysis in this study utilized the chi-square test, yielding a correlation coefficient of 0.050 (<0.05), indicating a significant relationship between parents’ parenting and adolescent self-esteem at SMA Negeri 2 Gading Rejo. It is expected that parents can provide appropriate and effective parenting so that children have a personality that can respect themselves and others.